Phase Evolution, Stability and Magnetic Behavior of Lightweight Al–Fe Aluminide-Based Nanocomposites Processed by Mechanical Alloying, Cryomilling, and Annealing - Balaji G.K.; Jain H.; Sherpa P.C.; Tripathy R.R.; Shadangi Y.; Shivam V.; Tripathi A.; Tiwari A.; Mukhopadhyay N.K. (My University, 2025)
Attempts are made to synthesize Al5Fe2 aluminide-based composites by mechanical alloying (MA) and cryomilling (CM). The XRD and TEM results of the milled samples confirm the formation of a major B2-AlFe phase (0.2887 ± 0.0003 nm; cP2) along with the minor amount of Al5Fe2 phase. Nanocrystalline grains of ≈16 nm and an average particle size of 4.0 ± 0.36 μm are evident. A significant refinement in the crystallite size (≈10 nm) and average particle size (1.0 ± 0.03 μm) is achieved after 10 h CM of 60 h MAed powder. CM enhances the phase fraction of the Al5Fe2 phase. The DSC thermogram discerns three exothermic heating events due to phase transformation. These can be corroborated by the structural transformation of the B2-AlFe phase to the orthorhombic Al5Fe2 phase. The phase obtained as a result of 60 h of MA transforms to orthorhombic Al5Fe2 along with a minor amount of pre-existing B2-AlFe structure after annealing at 600 °C. It becomes more stable after annealing at 900 °C. Further, the 60 h milled sample displays soft ferromagnetic properties. The saturation magnetization decreases on CM and annealing due to phase transition from B2-AlFe to Al5Fe2 phase. Coercivity is reduced when the MA sample is annealed due to an increase in crystallite size and a reduction in lattice strain. © 2024 Wiley-VCH GmbH.